2004
DOI: 10.1177/039463200401700310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia Pneumoniae in Atherosclerotic Coronary Arteries

Abstract: Chlamydia pneumoniae has recently been associated with the development of coronary heart diseases by sero-epidemiological studies and by direct detection of the organism in atherosclerotic tissues. The aim of our study was to employ a semi-nested PCR approach to investigate the presence of C. pneumoniae in both normal and atherosclerotic coronary arteries of humans obtained at autopsy. Moreover, we have evaluated the role of infection with C. pneumoniae in relation to the extent of coronary atherosclerosis. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Data summarized from 43 studies showed a high prevalence of C. pneumoniae (46% of 1852 specimens) in atheromatous arteries and a low prevalence (b1% of more than 239 specimens) in healthy arteries [2]. It has also been shown that advanced atherosclerotic lesions harbored C. pneumoniae DNA more frequently than mild atherosclerotic lesions [34][35][36]. Whether the presence of C. pneumoniae in human atheroma is merely an innocent bystander or a pathological process that initiates and accelerates atherosclerosis is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Data summarized from 43 studies showed a high prevalence of C. pneumoniae (46% of 1852 specimens) in atheromatous arteries and a low prevalence (b1% of more than 239 specimens) in healthy arteries [2]. It has also been shown that advanced atherosclerotic lesions harbored C. pneumoniae DNA more frequently than mild atherosclerotic lesions [34][35][36]. Whether the presence of C. pneumoniae in human atheroma is merely an innocent bystander or a pathological process that initiates and accelerates atherosclerosis is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As well as in vitro studies, confirmation that C. pneumoniae-infected peripheral blood mononuclear cells can be found in vivo has also been reported (16,(25)(26)(27). The evidence linking C. pneumoniae infection with atherosclerosis has led to several therapeutic intervention trials in patients with established coronary heart disease (28).…”
mentioning
confidence: 90%
“…In 1992, Shor et al (14) were the first to identify C. pn eumoniae by EM and ICC in atherosclerotic coronary plaques. So far a large number of studies (7,(15)(16)(17) have been published on the detection of C. pneumoniae in vascular tissue by PCR. However, the frequency of positive results varies considerably (from 0 to 100%) among the studies because no standardized PCR assays are available yet.…”
mentioning
confidence: 99%
“…Evidence for the presence of the organism in the atherosclerotic lesions has emerged from more than 40 studies using immunohistochemistry, electron microscopy and amplification of chlamydial DNA by polymerase chain reaction (PCR) (8,(15)(16)(17). Recently several studies have shown the presence of C.…”
mentioning
confidence: 99%